Perilaku Penelusuran Informasi Mahasiswa Dalam Pemanfaatan Media Video Online dengan Pendekatan Uses and Gratification - Franindya Purwaningtyas; Juni Yanti; Doni Sabdan Tanjung; Rizki Abdi Pulungan; Thoyyib Baihaqy (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to describe information seeking behavior through online video media by students of the Faculty of Letters, University of North Sumatra and the information needs of students of the Faculty of Computer Science and Information Technology, University of North Sumatra with the Uses and Gratification Approach through online video media. This research uses a quantitative approach with a descriptive study type. The research data is in the form of analysis results regarding information seeking behavior through online video media and information needs with the Uses and Gratification approach through online video media. Data collection was carried out using questionnaires and interviews. Instruments used to collect data using questionnaires and structured interviews. Based on the research results, it is concluded as follows. First, students of the Faculty of Computer Science and Information Technology are able to search for information through online video media with coherent stages, namely starting, chaining, browsing, monitoring, differentiating and extracting. Second, students are able to meet information needs with the Uses and Gratification approach starting from cognitive needs, affective needs, personal integration needs, social integration needs and escape needs. Keywords: Student Information, Online Video Media, Uses and Gratification